ANALISIS PENGARUH LEVERAGE, LIKUIDITAS, PERPUTARAN MODAL KERJA, DAN PERTUMBUHAN PENJUALAN TERHADAP PROFITABILITAS PERUSAHAAN (Studi pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di BEI pada Tahun 2009-2013) - Ibrahim, Achmad Taufik; Widyarti, Endang Tri (Diponegoro Journal of Management, 2015)
This study is performed to examine the effect of leverage, Current Ratio (CR), Working Capital Turnover (WCT), and growth toward Return On Asset (ROA) in consumer goods industry that is listed in BEI. The objective of this study is to analyze the effect of the company financial ratios performance leverage, Current Ratio (CR), Working Capital Turnover (WCT), and growth toward Return On Asset (ROA) in consumer goods industry that is listed in BEI over period 2009-2013.Purposive sampling is used on this research with criterion the company that represents their financial report oever period 2009-2013. The data is obtained based on Indonesian Capital Market Directory (ICMD) dan Indonesian Stock Exchange (IDX) publication. Sample of this research amount of 29 companies from 38 consumer goods indutry those are listed in BEI. Multiple regression and hypothesis test using t-statistic and f-statistic. In addition, classical assumption test also performed including normality test, multicolinearity test, autocorrelation test ,and heteroscedasticity test.This research results that leverage has significantly negative effect on Return On Asset (ROA), Current Ratio (CR) and growth are not significant to Return On Asset (ROA), and Working capital Turnover (WCT) has significant positive effect on Return On Asset (ROA). We suggest for consumer goods industry in order to give more attention to assets, liabilities, and working capital. On this research, Working Capital Turnover shows influencing variable toward Return On Asset (ROA) that pointed by the amount of beta standardized coefficients value 0.386, growth are 0.033, Current Ratio (CR) are -0.012, and leverage are -0,470.